2019
DOI: 10.1186/s13018-019-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt inhibitor partly decreases TNF-α-induced activation of fibroblast-like synoviocytes in osteoarthritis

Abstract: BackgroundThe Cadherin-11 and PI3K/Akt pathway are increasingly recognized as the potential therapeutic target of osteoarthritis (OA) synovitis. The study aimed to investigate the role of PI3K/Akt signaling pathway in the expression of Cadherin-11 and migration and invasive capacity of fibroblast-like synoviocytes (FLS) of OA patients under stimulation of TNF-α and to explore the effect of the PI3K/Akt inhibitor and Cadherin-11 antibody in the therapy of the collagenase-induced osteoarthritis (CIOA) mice.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Feldman has demonstrated that the PI3K/Akt pathway can be activated by several cytokines (TNF-α in RA synoviocytes) 34 . Our previous research also confirmed that inflammatory factors can activate the PI3K/Akt pathway in OA FLS 16 . In the current study, the results showed that IL-1β or TNF-α up-regulated the expression of cadherin-11 in PVNS FLS through the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Feldman has demonstrated that the PI3K/Akt pathway can be activated by several cytokines (TNF-α in RA synoviocytes) 34 . Our previous research also confirmed that inflammatory factors can activate the PI3K/Akt pathway in OA FLS 16 . In the current study, the results showed that IL-1β or TNF-α up-regulated the expression of cadherin-11 in PVNS FLS through the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 76%
“…In RA, studies have shown that cadherin-11 can stimulate FLS to produce inflammatory cytokines and matrix metalloproteinase 15 . Furthermore, inhibiting cadherin-11 can reduce the migration and invasion ability of OA FLS, and cadherin-11 antibodies attenuated synovitis and cartilage damage in an animal model of OA 16 . However, it remains unclear whether cadherin-11 is involved in the pathogenesis of PVNS and related to the high recurrence, invasion, migration, and cartilage destruction ability of PVNS FLS.…”
Section: Introductionmentioning
confidence: 98%
“…Several inhibitors that specifically target signaling pathways by inhibiting key proteins and upstream regulators in the pathway have shown therapeutic potential for treatment of OA in pre-clinical studies [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Allicin alleviates the progression of OA by inactivating the PI3K/AKT/NF-jB pathway [15]. Blocking PI3K/AKT signaling can reduce post-traumatic OA or tumor necrosis factor-a-induced OA [16,17]. Thus, blocking this pathway could be a promising treatment strategy for KOA.…”
mentioning
confidence: 99%